Oncogenic Role of PVT1 and Therapeutic Implications - Onagoruwa, Onayemi Titilayo; Pal, Gargi; Ochu, Chika; Ogunwobi, Olorunseun O. (Frontiers in Oncology, 2020)
PVT1, a long non-coding RNA has been implicated in a variety of human cancers. Recent advancements have led to increasing discovery of the critical roles of PVT1 in cancer initiation and progression. Novel insight is emerging about PVT1’s mechanism of action in different cancers. Identifying and understanding the variety of activities of PVT1 involved in cancers is a necessity for the development of PVT1 as a diagnostic biomarker or therapeutic target in cancers where PVT1 is dysregulated. PVT1’s varied activities include overexpression, modulation of miRNA expression, protein interactions, targeting of regulatory genes, formation of fusion genes, functioning as a competing endogenous RNA (ceRNA), and interactions with MYC, among many others. Furthermore, bioinformatic analysis of PVT1 interactions in cancers has aided understanding of the numerous pathways involved in PVT1 contribution to carcinogenesis in a cancer type - specific manner. However, these recent findings show that there is much more to be learned to be able to fully exploit PVT1 for cancer prognostication and therapy. In this review, we summarize some of the latest findings on PVT1’s oncogenic activities, signaling networks and how targeting these networks can be a strategy for cancer therapy.